Creation of a national map of organic carbon stocks in the soils of Ukraine - Plisko, I.V.; Bihun О.M.; Lebed, V.V.; Nakisko, S.G.; Zalavskyi, Yu.V. (AgroChemistry and Soil Science, 2018)
The article presents a step-by-step process of building a national organic carbon stock map, which created with the Global Soil Partnership (GSP) assistance in accordance with the requirements of the Agreement between the Food and Agriculture Organization of the United Nations (FAO) and the NSC "ISSAR named after O.N. Sokolovsky". It is described in detail the method of data collection and processing, preparation of auxiliary raster layers and spatial modeling in accordance with the digital methodology of soil mapping. The data, representative of the country soil cover on the map were collected from 16 research and scientific institutions. The ecological components which used for spatial modeling encompass most of the factors that influence the distribution of carbon, such as the type of soil, parent rock, relief, climate, biomass, and land use. Satellite images of high resolution in the infrared spectrum have been used to improve prediction. Simulation of the SOC distribution was performed using the Random Forest method, which allowed creating a map with permissible error for the chosen methodology. The first national map of soil organic carbon stocks in the upper layer thickness 0-30 cm was presented in high-resolution (1 km x 1 km) and integrated into the Global Soil Organic Carbon Map (GSOC).